In vitro cytotoxicity and cytogeneticity assay measuring the mutagenicity induced as effect of Cell phone radiation - LOHINY B,; SWETHA M,; VASANTHA KUMAR T,; KALYAN KUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Mutagenicity caused by mobile phone radiations were investigated in this study. Ames test determines the mutations caused due to the chemical or substance in the Salmonella with the utilization of specific bacterial strain. The bacterial reverse mutation assay detects the mutational reversion of his-dependent Salmonella to his-independent colonies. Mutation causing radiation increases the frequency of occurrence of his-independent colonies. MTT spectrophotometric assay determines the ability of viable cells to convert a soluble tetrazolium salts into insoluble formazan precipitate. The reaction converts yellow salts to blue formazan crystals that can be dissolved in an DMSO whose concentration can be determined at 570nm. From the Ames test , it is concluded that the dose response curve using various various concentration shows that the mobile phone head speaker radiation was partially mutagenic at the range of 313 to 5000 µg/plate. For MTT assay, a significant concentration dependent 70% inhibition of HepG2 cells were detected at 0.625 mg/ml.